Pengaruh Islamic Corporate Social Responsibility (ICSR) dan Sharia Governance Terhadap Kinerja Bank Umum Syariah - Ashry Salamayrika Rahmawaty; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to examine the effect of Islamic Corporate Social Responsibility (ICSR) and Sharia Governance on the performance of Islamic commercial banks. This research is quantitative through time series and cross section data. The population in this study are Islamic commercial banks registered with the Financial Services Authority in 2015-2019. By using purposive sampling method, there are 8 Islamic commercial banks as research samples. Performance variables were measured using Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). The ICSR variable is measured using the ISR index and the Sharia Governance variable is measured using the number of Sharia Supervisory Board meetings. The analytical method used is multiple regression analysis. The results of this study indicate that ICSR has no significant effect on ROA, Sharia Governance has a positive and significant effect on ROA, ICSR has no significant effect on ROE, Sharia Governance has a positive and significant effect on ROE, ICSR has a positive and significant effect on NIM, Sharia Governance has a negative and significant effect on NIM, ICSR has no significant effect on CAR, and Sharia Governance has a significant and negative effect on CAR.